Uso do ensaio de desgaste por micro abrasão para avaliação da abrasividade de partículas de alumina e carbeto de boro - Rosso, Tiago Alexandre (2017)
Manufacturing processes that use abrasion for material removal are constantly discussed in the literature. However, the abrasiveness, or the ability of material removal by particles has not been widely discussed in the literature specifically for micrometric particles. This removal capacity can be attributed to changes in the particle concentration, geometry, hardness and size distribution in the fluid abrasive. Therefore, a better understanding of the particles abrasiveness is necessary for a proper characterization of the modes and mechanisms acting in the process, since the abrasive selection is a significant economic factor in several manufacturing processes, such as grinding and hydroerosive grinding. The purpose of this work is to use the micro abrasion wear test to evaluate the abrasiveness of alumina and boron carbide particles. Samples of AISI D2 steel (677 HRC) and balls with 25.4 mm diameters quenched and tempered AISI 52100 steel were used. Tests were performed with different abrasives of similar sizes and with the same abrasive of different sizes to verify the influence of the abrasive concentration, ball rotation and wear and test time. Particle size distribution was determined by laser diffraction in terms of frequency distribution and cumulative frequency volumes. Moreover, the particle geometry characterization was also determined using the SPQ factor (Spike value) using a Matlab computer program. The size distribution indicated a higher percentage of fine particles for boron carbide and a higher percentage of coarse particles for alumina. The mean SPQ value was higher for boron carbide than for alumina with different average sizes. However, for different abrasives with similar average size, the alumina presented a bigger value for the parameter. This bigger value suggests a higher material removal capacity. The results show that test time is responsible for a change in the wear mode. Al2O3 particles presented a lower abrasiveness when compared to B4C particles because the wear coefficient was bigger for B4C after reaching the steady state regime. An increase in abrasive concentration and in test time led to a growth in material volume wear for both abrasives, while an increase in the ball rotation did not provide a significant increase in the material volume removed. The particles and specimen hardness and the abrasives size and angularity were used to discuss the causes of the steady state regime occur at different times for the two abrasives.